Chondroid tenosynovial giant cell tumor of the temporomandibular joint: A rare case report - Anbinder, Ana Lia [UNESP]; Geraldo, Barbara Maria Corrêa [UNESP]; Guimarães Filho, Rubens; Pereira, Débora Lima; de Almeida, Oslei Paes; Carvalho, Yasmin Rodarte [UNESP] (FapUNIFESP (SciELO), 2017)
Tenosynovial giant cell tumor of diffuse type (TGCT-d) or pigmented villonodular synovitis (PVNS) is a locally aggressive lesion that mostly affects the joints of long bones. Chondroid tenosynovial giant cell tumor (CTGCT) or PVNS with chondroid metaplasia is a rare distinct subset of synovial tumors that has a predilection for the TMJ. We report a rare case of CTGCT in the TMJ, initially misdiagnosed as temporomandibular disorder (TMD). A 51-year-old woman was referred to the surgeon with the chief complaint of TMJ pain for 5 years and a past history of an unsuccessful TMD treatment. Extraoral examination revealed discrete preauricular swelling and restricted mandibular range of motion. Panoramic radiograph and computerized tomography showed destruction of the mandibular fossa and condyle. Histologically, the tumor was composed by large mononuclear cells with prominent eosinophilic cytoplasm and grooved nuclei, small histiocytoid cells, osteoclast-like multinucleated cells, brown pigmentation and areas of chondroid metaplasia. Morphological and immunohistochemical characteristics lead to the final diagnosis of CTGCT. The rarity of CTGCT could be attributed to the lack of recognition of this lesion, with cases diagnosed as chondroblastomas, synovial chodromatosis and chondrosarcoma. The patient received immediate reconstruction and recurrence was found 22 months after initial intervention. TGCT-d and CTGCT of the TMJ can present similar symptoms to TMD, but clinicians must distinguish both lesions by complete examination, imaging and, when necessary, histopathologic evaluation.
Keywords: Chondroblastoma; Giant cell tumors; Pigmented villonodular synovitis; Synovium; Temporomandibular joint